A COMPARATIVE STUDY OF THE ACADEMIC PERFORMANCE OF COMMUNITY COLLEGE TRANSFER STUDENTS AND NATIVE STUDENTS AT SELECTED STATE UNIVERSITIES IN NORTH CAROLINA - Palmer, Vera Jane (East Carolina University, 2011)
Students, who complete their first two years of higher education at community colleges, must be prepared for the rigorous coursework at four-year institutions. The purpose of this study was to provide a comprehensive update and to determine if there were differences in the academic performance of North Carolina native students and North Carolina community college transfer students who began their higher education matriculation at selected community colleges in North Carolina and then transferred to state universities in the same state.   Using secondary data from statewide databases of student records with information on North Carolina community colleges and University of North Carolina institutions, this study investigated and analyzed data on academic performance as measured by grade point averages and average credit hours attempted for each year under study.  The findings from this study indicated that North Carolina community college transfer students who completed the requirements for associate degrees from the college transfer curriculum performed as well as native juniors as measured by grade point averages. However, the native students attempted more credit hours during their matriculation at the state universities than did their community college transfer counterparts.
Keywords: Educational leadership; Higher education; Academic performance; Community college transfer students; Native students; Student adjustment--North Carolina; College students--North Carolina; Community college students--North Carolina; Transfer students--North Carolina; Academic achievement--North Carolina